National integration and local power in Japan - Takao, Yasuo (Routledge, 2020)
This book offers a new study of local government in Japan. There is an enormous amount of information about Japanese local government that has not yet appeared in English. With the author’s local familiarity, elected local officials and local residents have been extraordinarily open and forthcoming. This allows a rethinking of the topic by mobilising a multitude of solid factual material. Japan has dealt with the dramatically increased public sector, but has done so in a setting of institutional centralisation. How has central authority sought to find ways of managing the continuous expansion of state activities? How have local authorities responded to central government’s initiative in integrating state administration? The answers the book gives to these questions present an alternative understanding of Japanese local government.